Health and psychosocial effects of flexible working hours - Daniela Janssen; Friedhelm Nachreiner (Universidade de São Paulo, 2004)
OBJECTIVE: To examine whether any impairments in health and social lives can be found under different kinds of flexible working hours, and whether such effects are related to specific characteristics of these working hours. METHODS: Two studies - a company based survey (N=660) and an internet survey (N=528) - have been conducted. The first one was a questionnaire study (paper and pencil) on employees working under some 'typical' kinds of different flexible working time arrangements in different companies and different occupational fields (health care, manufacturing, retail, administration, call centres). The second study was an internet-based survey, using an adaptation of the questionnaire from the first study. RESULTS: The results of both studies consistently show that high variability of working hours is associated with increased impairments in health and well-being and this is especially true if this variability is company controlled. These effects are less pronounced if variability is self-controlled; however, autonomy does not compensate the effects of variability. CONCLUSIONS: Recommendations for an appropriate design of flexible working hours should be developed in order to minimize any impairing effects on health and psychosocial well-being; these recommendations should include - besides allowing for discretion in controlling one's (flexible) working hours - that variability in flexible working hours should be kept low (or at least moderate), even if this variability is self-controlled. OBJETIVO: Investigar se ocorre prejuízo à saúde e à vida social com diferentes tipos de horas de trabalho flexíveis e se há relação entre estes efeitos e características específicas das horas de trabalho. MÉTODOS: Foram realizados dois estudos, uma pesquisa em uma empresa (N=660) e outra pela Internet (N=528). O primeiro estudo consistiu de um questionário (papel e lápis) aplicado a funcionários sujeitos a diferentes ajustes "típicos" de horas de trabalho flexíveis em empresas e áreas ocupacionais diversas (área da saúde, fábrica, comércio varejista, administração, serviços de central telefônica). O segundo estudo consistiu em um levantamento pela Internet, usando-se uma versão adaptada do questionário do primeiro estudo. RESULTADOS: Os resultados de ambos os estudos demonstraram de modo compatível que a alta variabilidade das horas de trabalho está associada a um maior prejuízo da saúde e do bem-estar, sobretudo se esta variabilidade é controlada pela empresa. Os efeitos são menos acentuados se a variabilidade é autocontrolada; a autonomia, no entanto, não contrabalança os efeitos da variabilidade. CONCLUSÕES: Devem ser feitas sugestões para um planejamento adequado de horas de trabalho flexíveis para minimizar os efeitos prejudiciais à saúde e ao bem-estar psicossocial. Além de permitir o uso de um critério pessoal para o controle de horas de trabalho (flexíveis), a variabilidade das horas de trabalho flexíveis deve ser pequena (ou, no mínimo, moderada), mesmo se ela for autocontrolada.